2001
DOI: 10.3923/pjbs.2001.374.377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Regulators on Plantlet Regeneration and Bulbing in Onion (Mum cepa L.) in vitro

Abstract: The experiment was conducted to study the effect of growth regulators on plantlet regeneration and bulbing of onion in vitro. Results from the experiment showed that both plantlet regeneration and bulbing were greatly affected by growth regulators or their combinations. It was found that shoot induced from twin scale in 0.1 mg/l NAA was with a percentage of 93% and per explant shoot rate of 0.84. A combination of 0.1 mg/I NAA + 2 mg/I 4PU 30 induced 89% shoot regeneration from twin scale. The highest per expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The presence of plant growth regulator (BAP and NAA) is important to stimulate explant growth and develpoment on shallot micropropagation. Earlier report [13] showed an increase in percent shoot formation and number of shoot per explant was observed when the concentration of BAP+NAA was increased and in the current study it is also confirmed that cytokinins were the most determining hormones involved in the regeneration of shoots in shallot. The growth of garlic shoots was stimulated in medium culture with 0.5 ppm BAP [12].…”
Section: Advances In Biological Sciences Research Volume 13supporting
confidence: 88%
“…The presence of plant growth regulator (BAP and NAA) is important to stimulate explant growth and develpoment on shallot micropropagation. Earlier report [13] showed an increase in percent shoot formation and number of shoot per explant was observed when the concentration of BAP+NAA was increased and in the current study it is also confirmed that cytokinins were the most determining hormones involved in the regeneration of shoots in shallot. The growth of garlic shoots was stimulated in medium culture with 0.5 ppm BAP [12].…”
Section: Advances In Biological Sciences Research Volume 13supporting
confidence: 88%
“…On the contrary, in some other species, a moderate dosage of auxin is impressive, and the high content is an inhibitor (Tanimoto 2005;Kondhare et al 2021). Khalid et al (2001) found that plantlet regeneration and bulbing of Allium cepa L. was notable by increasing the concentration of NAA up to 0.3 mg•L −1 based on the twin-scaling technique under in vitro condition; however, the efficacy in greater concentrations was inverse. Xu et al (2020) investigated the processes of bulblet initiation (0-7 days after treatment) and bulblet development (7-60 days after treatment) in Lycoris radiata Herb.…”
Section: Discussionmentioning
confidence: 99%